AGE OF ROCKS IN THE BAIKAL-MUYA FOLDBELT - Rytsk E.Yu.; Rizvanova N.G.; Krimsky R.Sh.; Shalaev V.S.; Amelin Yu.V.; Mitrofanov G.L.; Mitrofanova N.N.; Perelyaev V.I. (My University, 2001)
The presented results of U-Pb zircon dating (those for individual grains included) and Sm-Nd isochron ages for whole-rock samples and mineral fraction characterize magmatic complexes of the Muya segment of the Baikal-Muya foldbelt. New isotopic dates indicate the Late Riphean-Vendian age of volcanogenic-sedimentary and igneous rocks, which have been formed in the Muya segment during the Early Baikalian (from about 1.0 to 0.8 Ga) and Late Baikalian (0.8-0.62 Ga) stages of tectogenesis. The distinguished syntectonic granitoids of the Early Baikalian stage mark a collision event that happened 0.8 Ga ago. The results obtained are used to refine the traditional scheme of Precambrian stratigraphy and magmatism in the Middle Vitim Mountains.
Keywords: Precambrian; Riphean; Vendian; Baikal-Muya foldbelt; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский; Докембрий; Precambrian; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей